Codin' for the web : a designer's guide to developing dynamic web sites - Wyke-Smith, Charles (Voices., 2006)
Here to help designers create sites that not only work, but work well is this guide to Web programming basics from author Charles Wyke-Smith. Web designers need to understand the code that serves as the foundation of their sites. Wyke-Smith ensures they do by teaching designers that all dynamic Web sites consist of essentially three components. This guide covers everything from Web coding concepts and principles to building sites, designing visual interfaces, developing databases, and more.--[book cover].